The Effect Of Profitability, Leverage, And Company Size On Company Value In Manufacturing Companies Listed On The Indonesia Stock EXCHANGE (Consumer Goods Industry Sub-Sector, 2020-2024 Period) - Aiko Aurelia Nur Amri; Dudi Pratomo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Firm value is an indicator that reflects investors' perceptions of a company's performance and future prospects. This study aims to analyze the effect of profitability, leverage, and firm size on firm value in manufacturing companies in the Consumer Goods Industry sub-sector listed on the Indonesia Stock Exchange for the 2020–2024 period. This study uses a quantitative approach with secondary data obtained from the companies' annual financial reports. The research sample was selected using a purposive sampling technique based on predetermined criteria. Profitability is proxied using Return on Assets (ROA), leverage using the Debt to Equity Ratio (DER), firm size using the natural logarithm of total assets, while firm value is proxied by Price to Book Value (PBV). Data analysis was performed using panel data regression with the help of EViews 12 software. The results show that simultaneously, profitability, leverage, and firm size have a significant effect on firm value. Partially, profitability does not have a significant effect on firm value, leverage has a positive and significant effect on firm value, while firm size does not have a significant effect on firm value. These findings indicate that investor decisions in assessing a company are more influenced by funding structure than profitability or firm size.